A study of Palestinian students’ perspectives on their willingness to communicate with foreigners in English - Qaddumi, Husam; Smith, Matt (Association for Scientific Computing Electrical and Engineering(ASCEE), 2024)
Willingness to communicate (WTC) in a foreign language (FL) has become one of the most important affective variables in the context of learning a foreign language including motivation, anxiety, learner beliefs, and many others. This study looks into the underlying causes of English students' propensity to speak English, particularly in higher education settings after the Covid-19 pandemic. The study also determines the WTC of college students in English classes. One thousand students who are presently enrolled in English programs at Palestinian universities constitute the study's participants. The study employed a descriptive research design: a questionnaire was used to collect the data, which were then analyzed using statistical analysis methods in the SPSS program. The findings of the study indicated that the two primary factors negatively affecting the WTC among English learners in Palestine's colleges and universities were personality traits and a lack of confidence in one's speaking abilities.